You are on page 1of 1

# Determination of the function f (t).

Dimitri Deliyiannis
Physics Department,
Aristotle University
of Thessaloniki.
email: deliyiannis@yahoo.gr
(Dated: July 13, 2015)

The dimensionless form of the cosmological equations
are
Dimensionless F luid equation :
f0
ρ¯0
+3=
ρ¯
f
Dimensionless Acceleration equation :
¯H
¯ 0 = −3¯
2H
ρ
Dimensionless F riedman equation :
¯ 2 = ρ¯ 0
H
1 + ff

y=

1

(1)

y0

1+y0 e
y0
e4τ
− 1+y
0

(6)

From the dimensionless Friedman equation

(2)

¯2 =
H

ρ¯
0
1 + ff

¯2 =
H

ρ¯
1+y

¯ 02 =
H

ρ¯0
1 + y0

(3)

By differentiating equation (3) with respect to the logarithmic time variable we obtain
0

ρ¯0
(f 0 /f )
− ρ¯
2
0
1 + f /f
(1 + f 0 /f )

¯H
¯0 =
2H

y0 = ρ0 − 1

We use equation (1) to eliminate ρ¯0

Subtituting the last equation in (6)and replacing y with

0

f0
f

0

0

¯H
¯ 0 = ρ¯ (f /f ) − 3 − ρ¯ (f /f )
2H
2
1 + f 0 /f
(1 + f 0 /f )

(4)

ρ0 − 1) e4τ
f0
=
f
ρ¯0 − (¯
ρ0 − 1) e4τ

Comparing equations (2) and (4)
0

−3¯
ρ = ρ¯

We solve equation (7) with respect to f (τ ) and we obtain

(f 0 /f )
(f 0 /f ) − 3
− ρ¯
2
0
1 + f /f
(1 + f 0 /f )

dlnf

ρ0 − 1)e4τ
=

ρ¯0 − (¯
ρ0 − 1)e4τ

and finally 

f0
f 

0

f0
=4
f  

f0
1+
f

(5)
Z

f

Z

τ

dlng =
We set

f0
f

f0

= y and (5) becomes
y 0 = 4y(1 + y)

ln
dy
= dτ
4y(1 + y)
Z

y

y0

dz
=
4z(1 + z))

Z

0

ρ0 − 1)e4x
dx
ρ¯0 − (¯
ρ0 − 1)e4x

1
f
= − ln[¯
ρ0 − (¯
ρ0 − 1)e4τ )]
f0
4

and knowing that f0 = 1
f (τ ) = [¯
ρ0 − (¯
ρ0 − 1)e4τ ]−1/4

τ

0

(7)

(8)